Herstellung von mehrschichtigem Graphen in einer Scheibenschwingmühle. Issue 4 (27th February 2018) - Trüe, Michael; Aman, Sergej; Müller, Peter; Hintz, Werner; Hirsch, Sören
Abstract: Optimal process conditions for the delamination of multilayer graphene are realized with a vibratory disk mill, in which a highly viscous liquid consisting of sugar and graphite particles is comminuted. The conditions are investigated, in which shear forces are generated in the process in the vibratory disk mill. Graphene sheets with layer thicknesses of 2 – 10 layers are obtained. The multilayer graphene can be used in the production of lithium‐ion accumulators.